Impact of Pet Ownership and Relationships on Human Psychological Health and Function - Bhatia, (Maj) Deepak; Bhatia, Akansha; Sarma, Dhritiman (Gyan Management Journal, 2022)
Numerous studies have examined the effects of “pet /companion ownership  and pet interactions on human psychological health and function”. Recent  study on “the benefits of pets and human-animal interaction for mental  health has discovered new benefits for managing stress, depression, and  post-traumatic stress, as well as for stress reduction”. Interacting with  animals has been demonstrated to reduce cortisol levels (a hormone  associated with stress) and blood pressure. Other studies have discovered  that pets help alleviate feelings of isolation, promote emotions of social  support, and improve your happiness. “The biopsychosocial model has been  widely used for over 40 years to describe how biological, psychological, and  social processes interact to affect human health and wellbeing. Biological  impacts are physiological changes, including blood pressure, cortisol,  and heart rate, among others. Among the psychological influences are  personality, disposition, and emotions. The term social influences refer  to cultural, socioeconomic, and social ties with others, as well as family  dynamics and aspects related”.
Keywords: Pet; Companion; Ownership; Human Health